Advancing careers through 'merit': a rationalized-sensemaking narrative in hierarchical organizations. Issue 4 (3rd July 2020) - Pérez, Andrés; Sabelis, Ida
ABSTRACT: This contribution provides an in-context exploration of how middle-managers make sense of their career progress, and particularly focuses on 'merit' to understand how careers are driven in a hierarchical organization. The study exposes 'merit' as a fragmented and individualized construction that links back to the participants' broader life ambitions and identity footprint. It also shows a tendency for maintaining trust in 'merit' above other circumstantial and opportunity factors, even in face of events which undermine the application of the merit-based principle. 'Merit' is hence portrayed to be a rationalized narrative in careers' trajectory; a marker used by participants to make sense of events in a coherent manner, consequently experiencing self-efficacy and reducing uncertainty. The findings add complexity to the 'meritocracy' debate, calling for new critiques which address its underlying inequality dimension while also contemplating the individual psychological purpose driving 'merit' beliefs.